First-in-human HIV-remission studies: reducing and justifying risk - Dresser, Rebecca (Journal of medical ethics, 2017)
Interest and excitement surround the possibility of developing measures that produce sustained or permanent HIV remission in infected individuals. First-in-human (FIH) trials are one step in exploring this possibility. Initial human trials raise the usual ethical issues associated with human research, and a set of distinct issues. Because the potential direct benefits to FIH trial volunteers will be either small or non-existent, trial risks must be justified by the social value of the information the trials are expected to produce. To minimise and justify risks, researchers must have solid preclinical evidence that FIH trials will be safe and produce information relevant to human health improvements. Researchers must also adopt adequate study safeguards to protect FIH subjects. An ethically defensible study population must be selected as well.